Preference Function Reconstruction for Multiple Criteria Decision Making Based on Machine Learning Approach - Lyubchyk, L. M.; Grinberg, G. L. (Springer International Publishing, 2014)
The problem of expert preference function reconstruction in decision making process of multicriterion comparative assessment of set of object is considered. The problem is reduced to integral indicator identification using available data of object’s performance indexes measurements as well as expert estimation of integral indicators values for each object and feature weights. Based on machine learning approach and expert estimations concordance technique, the solution of preference function recovering problem is obtained in the form of optimal nonlinear object feature convolution.

Рассмотрена проблема восстановления функции экспертных предпочтений в процессе принятия решений многокритериальной сравнительной оценки множества объектов. Задача сводится к интегральной идентификации индикатора с использованием данных измерений показателей эффективности объекта, а также экспертной оценки значений интегральных индикаторов для каждого объекта и весов признаков. В результате использования метода машинного обучения и метода согласования экспертных оценок, была получена функция предпочтения в виде оптимальной нелинейной свертки.
Построение функции предпочтения для принятия решений по нескольким критериям с использованием машинного обучения
Keywords: machine learning; preference function reconstruction; expert; multicriterion comparative assessment